Para-Diplomacy in Time of Covid-19 - Luerdi Luerdi (Resolusi: Jurnal Sosial Politik, 2022)
The Novel Corona Virus Disease or COVID-19 has caused unprecedented huge impacts and affected all aspects of governance including the relations among countries. Amid the crisis, sub-national governments have demonstrated their international engagements and innovations in order to respond to the pandemic. Jakarta as the largest city and the capital of the Republic of Indonesia became the national attention in early of the pandemic due to its functional position as the main gate of international mobility. However, the region held an international event called the International Youth Championship while the pandemic still existed. This research aimed to describe the region’s objectives to carry out the event as a para-diplomacy practice. This research applied the qualitative research method with a descriptive analysis. In addition, the research utilized para-diplomacy concept as a theoretical tool to help describe such objectives. This research found that the regional government had a number of objectives in hosting the event; promoting the success of handing the COVID-19, promoting sports tourism in the post-pandemic, and introducing a new icon of the region. Those objectives belong to the economic and cultural dimension of para-diplomacy. This paper argues that Indonesian para-diplomacy is an asset inasmuch as the national government can harvest benefits from sub-national governments’ para-diplomatic activities.